2015
DOI: 10.1002/jhet.2337
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Alkylated Indolines and Indoles from Indoline and Aliphatic Ketones

Abstract: A survey of redox aminations of indoline with aliphatic ketones using bismuth nitrate as catalyst is described. A reaction of an equivalent amount of indoline and aliphatic cyclic and acyclic ketones provides a mixture of excessive alkylated indole derivatives over typically redox isomerization and reductive alkylation pathways while using of the five equivalent of indoline provides N-alkylated indolines as a reductive alkylation product. The desired N-alkyl indoles from the oxidation of N-alkyl indolines were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a recent article, Tunge et al synthesized N ‐aryl‐1‐aminoindoles from indolines with different nitrosobenzenes via intermolecular redox amination (Scheme ) . Recently, we also investigated the redox amination potential of both enolizable cyclic and acyclic ketones and benzylic ketones with indoline . Our results showed that the formation of N ‐alkyl substituted indole/indoline derivatives over competitive redox and reductive amination processes depending on the reaction condition and ketones.…”
Section: Introductionmentioning
confidence: 81%
“…In a recent article, Tunge et al synthesized N ‐aryl‐1‐aminoindoles from indolines with different nitrosobenzenes via intermolecular redox amination (Scheme ) . Recently, we also investigated the redox amination potential of both enolizable cyclic and acyclic ketones and benzylic ketones with indoline . Our results showed that the formation of N ‐alkyl substituted indole/indoline derivatives over competitive redox and reductive amination processes depending on the reaction condition and ketones.…”
Section: Introductionmentioning
confidence: 81%
“…Recently, we communicated our results to access N 1‐ and excessive substituted indoles via a competitive redox and reductive amination of indoline with enolizable aliphatic ketones (Scheme ) . Here, we report on our detailed results on the bismuth nitrate‐catalyzed redox amination of a wide range of benzylic ketones with indoline.…”
Section: Introductionmentioning
confidence: 92%
“…In 2015, Saracoglu and co-workers realized the synthesis of N-alkylindoles from indoline and aliphatic ketones. 30 While no reaction takes place with Brønsted acids such as benzoic acid or trifluoroacetic acid, bismuth nitrate pentahydrate was identified as a viable catalyst. In addition to the desired N-alkylindole products formed by the redox-amination, secondary byproducts from alkylation of the aromatic ring were also obtained.…”
Section: Review Synthesismentioning
confidence: 99%